(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Recently, the use of non-linear loads has expanded and covered different fields of electricity.Bridge rectifiers, line converters, and switching mode power supplies are the most important used nonlinearloads. Non-linear loads inject harmonic currents into the electrical grid. The grid currents andvoltages become non-sinusoidal having different types of disturbances. Active power filters have beenintroduced as efficient devices for power quality improvement as like as reactive power compensation.In this work, harmonic problem are introduced and discussed. The different harmonic solutions arepresented and discussed. The use of Series Active Power Filter for filtering the harmonics of the voltageis also discussed. The passive filters are used also for elimination of harmonic currents and voltages.The use of hybrid filters composed of parallel active power filter with passive filters, or series activepower filter with passive filters is applied and studied. Different studied filters and topologies areimplemented in MATLAB. Simulation results are tabulated and discussed.